Computer «ProNRS-І» System and Energy-Saving Problems in Ingot Metallurgy - A. N. Chichko; Yu. V. Yatskevich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Models for computer analysis of crystallization process in metallurgical ingots obtained as a result of continuous steel casting are proposed in the paper. Calculations of spatial distribution of temperatures, stresses and carbon in a steel ingot of 250x300 mm size have been made in respect of a real continuous steel casting machine.